2014
DOI: 10.1016/j.urolonc.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of multiparametric MRI in men with negative biopsy and elevated PSA level—Can it rule out clinically significant prostate cancer?

Abstract: PurposeTo assess the performance of multiparametric magnetic resonance imaging (mp-MRI) in patients with previous negative transrectal ultrasound (TRUS) guided prostate biopsy.Materials and methodsFifty-four patients with at least 1 previous negative TRUS prostate biopsy underwent mp-MRI in the form of T2-weighted, diffusion-weighted, and dynamic contrast-enhanced imaging. This was followed by transperineal template systematic prostate biopsies. Analysis was done based on 2 sectors per prostate, right and left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
78
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 20 publications
12
78
0
1
Order By: Relevance
“…Conversely, 3T MP-MRI with endorectal coil for the identification of suspicious prostate lesions and subsequent MRI/TRUS fusion-guided prostate biopsy has exhibited high levels of sensitivity and negative predictive values (>90%) in detecting clinically significant disease. 8,18 In the current study, we observed an overall CDR of 64.6% which is comparable to the 54% to 63% range reported in the literature. 11,19,20 We observed an AUC of 0.769 (95% CI, 0.703-0.834) for lesion suspicion level on MP-MRI in predicting high-grade CaP, which is 10 percentage points better than the PCPTHG AUC of 0.676 (95% CI, 0.592-0.751; P 5 .091).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Conversely, 3T MP-MRI with endorectal coil for the identification of suspicious prostate lesions and subsequent MRI/TRUS fusion-guided prostate biopsy has exhibited high levels of sensitivity and negative predictive values (>90%) in detecting clinically significant disease. 8,18 In the current study, we observed an overall CDR of 64.6% which is comparable to the 54% to 63% range reported in the literature. 11,19,20 We observed an AUC of 0.769 (95% CI, 0.703-0.834) for lesion suspicion level on MP-MRI in predicting high-grade CaP, which is 10 percentage points better than the PCPTHG AUC of 0.676 (95% CI, 0.592-0.751; P 5 .091).…”
Section: Discussionsupporting
confidence: 87%
“…However, it has been demonstrated that MP-MRI of the prostate exhibits a high negative predictive value of >90%. 18 Moreover, we previously validated the MRI/TRUS fusion-guided biopsy platform in a community setting, attesting to the reproducibility of results. 11 Furthermore, our images, which were obtained using 3T MRI with a 16-channel cardiac coil placed on the anterior pelvis and an endorectal coil, were of superior quality (for MRI parameters, see online supporting information).…”
Section: Discussionmentioning
confidence: 79%
“…A total of 8663 original studies in English were identified and 15 were analyzed. [2][3][4][6][7][8][23][24][25][26][27][28][29][30][31] The overall quality varied from low to moderate. Fourteen conference abstracts will require followup in future updated versions.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…• In three studies (n=570) 8,27,31 with a prevalence of CSPC of 18-34%, the ranges of sensitivity, specificity, positive predictive value, and negative predictive value of mpMRI to detect CSPC were 68-100%, 41-91%, 29-87%, and 79-100%, respectively.…”
Section: Key Evidencementioning
confidence: 98%
See 1 more Smart Citation